Analisis Kepercayaan pada Modal Sosial Pedagang Etnik Tiu Chiu dan Hokkian di Kawasan Pasar 16 Ilir Kota Palembang - Wijaya, Revi Vereyanthi; Yunindyawati, Yunindyawati; Purnama, Dadang Hikmah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Chinese traders are one of the many Ethnic Businessmen in Indonesia who have achieved success in various places in Indonesia including in Palembang City, this is inseparable from the Trust capital that has existed for generations. This research aims to analyze trust in the social capital of ethnic Tiu Chiu and Hokkien traders in the 16 Ilir Market Area of Palembang City. This research uses a qualitative method with a descriptive type. The results of this study indicate that trust in social capital has an important role in the progress and sustainability of businesses carried out by ethnic Tiu Chiu and Hokkian in trading, with the trust between fellow Tiu Chiu and Hokkian traders providing opportunities for ethnic Tou Chiu and Hokkian traders to develop. Trust, besides having to be instilled in traders, must also be given to customers so that they continue to trust and always buy goods belonging to ethnic Tiu Chiu and Hokkien traders in the 16 Ilir Market Area of Palembang City.